Evaluation of climate change resilience for Boston's rail rapid transit network. (August 2021) - Martello, Michael V.; Whittle, Andrew J.; Keenan, Jesse M.; Salvucci, Frederick P.
Highlights: Assessment of rail rapid transit resilience to climate change. Consideration of physical, topological, contextual aspects of system performance. Presentation of sea level rise (SLR) impacts on a rail rapid transit system. Sea level rise will create new flood pathways, inundating critical links and yards. Resilience assessments can inform decision makers and adaptation planning efforts. Abstract: Sea level rise (SLR) poses increasing flood risks to coastal cities and infrastructure. We propose a general framework of engineering resilience for infrastructure systems in the context of climate change and illustrate its application for the assessment of SLR impacts on the rail rapid transit network in Boston. Within this framework, projected coastal flood events are treated as exogenous exposure events, which interact with both physical and topological endogenous network characteristics. We consider contextual aspects of resilience by assigning relative importance to links based on passenger flows. Resilience is computed assuming a linear recovery model, neglecting recovery strategies. Using a reference 1–100 year coastal flood event we show decreasing resilience of the rail transit network as projected SLR increases. The proposed framework can be readily extended to consider more sophisticated performance models, recovery strategies, other perturbation events, and additional contextual factors, such as equity considerations.